SHI'AH: ANTARA KONTROVERSI DAN KONTRIBUSI TERHADAP DAKWAH ISLAM DI KOTA PALU - Samsinas Samsinas; Muhammad Alim Ihsan (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
This paper deals with Shi'ah in Palu with the focus on two main problems; first, how does Shi'ah emerge as a contradictory school of thought with the perception of Muslim community in Palu? Second, how does Shi'ah contribute to Islamic preaching in Palu? This study used qualitative method with science of da'wah approach. The findings show that Shi'ah which have emerged and developed in Palu are Ithna 'Ashariyyah and Fatimiyyah. Through such organization as IJABI and ABI, Shi'ah used a new strategy of Islamic preaching which is exclusive and constructive to show that Shi'ah is not a historical heritage which tends to make Shz'ah- Sunni conflict appear, but tends to make friend with other schools of thought. The strategy includes doing social activity which is directly felt by the public, without forcing them to be the followers of Shi'ah, and building good relationship with such Sunni-Islamic organizations as Alkhairaat and Darul ad- Da'wah wa al-Irsyad (DDI).